Conditional Properties of Estimators of Repeated Measurements Model (Type I) (Eurasian Journal of Physics,Chemistry and Mathematics, 2021)
This paper studies the conditional biases and mean squared errors of the repeated measurements model for two types 1 and 2 estimators.